Comparative analysis of genotypes of Helicobacter pylori strains in the Rostov and Astrakhan regions - V. M. Sorokin; R. V. Pisanov; A. S Vodop’janov; E. V. Golubkina; E. A. Bereznjak (Медицинский вестник Юга России, 2018)
Objective: to study the infection of the adult and children’s population of the Rostov and Astrakhan regions by the bacteria Helicobacter pylori, to determine the frequency of H. pylori pathogenicity factors in diﬀerent age groups of the population.Materials and methods: 118 adults and 112 children were examined. Te presence of H. pylori DNA and the pathogenicity factors of CagA and VacA in the biopsy material of the mucous membrane of the antrum of the stomach was determined by PCR.Results: a signifcantly smaller percentage of H. pylori–positive patients is characteristic of the child population. Te prevalent H. pylori genotype in the infant population is the avirulent genotype Vac s2m2 (60%) (χ2: p <0.005). Genotype CagA + VacAs1 VacAm1 is a marker of peptic ulcer for adult population of the Rostov region.Conclusion: Te conducted studies allowed to establish diﬀerences in infection of the population with H. pylori bacteria and the frequency of the distribution of virulent genotypes depending on the region, age and severity of the pathology.